Xrn1/Pacman affects apoptosis and regulates expression of hid and reaper. - Waldron, J.A.; Jones, C.I.; Towler, B.P.; Pashler, A.L.; Grima, D.P.; Hebbes, S.; Crossman, S.H.; Zabolotskaya, M.V.; Newbury, S.F. (Biology open, 2015)
Programmed cell death, or apoptosis, is a highly conserved cellular process that is crucial for tissue homeostasis under normal development as well as environmental stress. Misregulation of apoptosis is linked to many developmental defects and diseases such as tumour formation, autoimmune diseases and neurological disorders. In this paper, we show a novel role for the exoribonuclease Pacman/Xrn1 in regulating apoptosis. Using Drosophila wing imaginal discs as a model system, we demonstrate that a null mutation in pacman results in small imaginal discs as well as lethality during pupation. Mutant wing discs show an increase in the number of cells undergoing apoptosis, especially in the wing pouch area. Compensatory proliferation also occurs in these mutant discs, but this is insufficient to compensate for the concurrent increase in apoptosis. The phenotypic effects of the pacman null mutation are rescued by a deletion that removes one copy of each of the pro-apoptotic genes reaper, hid and grim, demonstrating that pacman acts through this pathway. The null pacman mutation also results in a significant increase in the expression of the pro-apoptotic mRNAs, hid and reaper, with this increase mostly occurring at the post-transcriptional level, suggesting that Pacman normally targets these mRNAs for degradation. Our results uncover a novel function for the conserved exoribonuclease Pacman and suggest that this exoribonuclease is important in the regulation of apoptosis in other organisms.